Differential Effects of Green Tea Powders on the Protection of Brown Tsaiya and Kaiya Ducklings against Trichothecene T-2 Toxin Toxicity - Tso, Ko-Hua; Lumsangkul, Chompunut; Cheng, Min-Chien; Ju, Jyh-Cherng; Fan, Yang-Kwang; Chiang, Hsin-I (Animals (Basel), 2021)
A 3-week feeding trial in a 3 × 2 × 2 factorial design was conducted with three concentrations (0, 0.5, and 5 mg/kg) of T-2 toxin (T-2) and two levels (0% and 0.5%) of green tea powder (GTP) supplements used in the diets of female brown Tsaiya ducklings (BTDs) and Kaiya ducklings (KDs), respectively. Breed had a significant effect on the growth performances and the relative weights of organs and carcass. In general, the growth performances of KDs were better than BTDs. The relative weights of organs and carcass of BTDs were typically heavier than those of KDs; however, the breast of KDs was heavier than those of BTDs. Both ducklings received 5 mg/kg of T-2 blended in the diet showed lower feed intake and body weight gain (BWG) in the second and the third week. The diet containing 5 mg/kg of T-2 and 0.5% GTP improved the BWG compared to those fed the diet supplemented with 5 mg/kg of T-2 without GTP in BTDs. Ducklings fed the diet containing 5 mg/kg of T-2 induced hypocalcemia and hypomagnesemia, as well as decreased concentrations of creatine phosphokinase and alkaline phosphatase. The concentrations of blood urea nitrogen (BUN) and glutamate oxaloacetate transaminase (GOT) were increased in KDs and BTDs fed the diet containing 5 mg/kg of T-2 without GTP, respectively. However, duckling diets containing 5 mg/kg of T-2 with 0.5% GTP lowered concentrations of BUN and GOT in the blood plasma of KDs and BTDs, respectively. The diet containing 5 mg/kg of T-2 increased the relative kidney weight but decreased the relative breast weight of ducklings. Enlarged gizzards and reduced relative leg weights were observed in BTDs fed the diets containing 5 mg/kg of T-2. In summary, BTDs are more sensitive than KDs in responding to T-2 toxicity and GTP detoxification. Green tea powder has detoxification ability and could potentially mitigate T-2 toxicity on BWG, BUN, and GOT in ducklings.